Vinculin Interacts with the Chlamydia Effector TarP Via a Tripartite Vinculin Binding Domain to Mediate Actin Recruitment and Assembly at the Plasma Membrane - Thwaites, Tristan R.; Pedrosa, Antonio T.; Peacock, Thomas P.; Carabeo, Rey A. (Frontiers in Cellular and Infection Microbiology, 2015)
The mammalian protein vinculin is often a target of bacterial pathogens to subvert locally host cell actin dynamics. In Chlamydia infection, vinculin has been implicated in RNA interference screens, but the molecular basis for vinculin requirement has not been characterized. In this report, we show that vinculin was involved in the actin recruitment and F-actin assembly at the plasma membrane to facilitate invasion. Vinculin was recruited to the plasma membrane via its interaction with a specific tripartite motif within TarP that resembles the vinculin-binding domain (VBD) found in the Shigella invasion factor IpaA. The TarP-mediated plasma membrane recruitment of vinculin resulted in the localized recruitment of actin. In vitro pulldown assays for protein-protein interaction and imaging-based evaluation of recruitment to the plasma membrane demonstrated the essential role of the vinculin-binding site 1 (VBS1), and the dispensability of VBS2 and VBS3. As further support for the functionality of VBD-vinculin interaction, VBD-mediated actin recruitment required vinculin. Interestingly, while both vinculin and the focal adhesion kinase (FAK) colocalized at the sites of adhesion, the recruitment of one was independent of the other; and the actin recruitment function of the VBD/vinculin signaling axis was independent of the LD/FAK pathway.